1959
DOI: 10.1084/jem.110.4.585
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Production of Two Capsular Polysaccharides by Pneumococcus

Abstract: In the preceding paper, the isolation and some characteristics of a pneumococcus manifesting binary capsulation were described (1). This organism, which was shown to produce two capsular polysaccharides, was derived by transformation of a non-capsulated mutant of pneumococcus Type III with deoxyribonucleates (DNA) of pneumococcus Type I. A noteworthy property of the SI-III cell is the production by it of approximately normal amounts of Type III polysaccharide in contrast to the markedly diminished or absent pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1960
1960
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…In a study of the UPPG dehydrogenase activity of Streptococcus pneumoniae strain R19, derived from capsular type II, Smith et al (1959) observed the marked instability of this enzyme and the low yields of UPPGA obtained with the experimental conditions used. It was considered possible that the low dehydrogenase activity might be a function of inactivation of the enzyme activity by hydrogen peroxide (H,OJ.…”
Section: Resultsmentioning
confidence: 99%
“…In a study of the UPPG dehydrogenase activity of Streptococcus pneumoniae strain R19, derived from capsular type II, Smith et al (1959) observed the marked instability of this enzyme and the low yields of UPPGA obtained with the experimental conditions used. It was considered possible that the low dehydrogenase activity might be a function of inactivation of the enzyme activity by hydrogen peroxide (H,OJ.…”
Section: Resultsmentioning
confidence: 99%
“…The essential role of the capsule in S. pneumoniae virulence was established through the study of spontaneous mutants, the genetic transfer of capsular serotypes, and the use of a type 3-specific depolymerase to remove the capsule prior to infection (6,22,29). Genetic transfer of capsular serotypes indicated linkage of the genes necessary for synthesizing a specific capsular polysaccharide, and recombination experiments confirmed those linkages (4,18,37,38). A role for unlinked genes was indicated by the transfer of the normal capsule phenotype from mutants that produced reduced levels of capsule (28).…”
mentioning
confidence: 99%
“…Nomendaure of Pnzumococcal Varients.--The nomenclature of pneumococcal variants employed will be that described in earlier publications (3)(4)(5). Mutants of noncapsulated variants producing capsules of C-like polysaccharide will be designated by the symbols denoting the parental noncapsulated strain followed by the symbol Cs; i.e., S-nC, is a variant of a noncapsulated strain of pneumoeoccns Type II which produces a capsule of soluble Clike polysaccharide.…”
Section: Methodsmentioning
confidence: 99%
“…It is known from earlier experiments that strains S-m4 and S-ms both possess the capsular genome of pneumococcus Type HI with mutations at different sites in the cistron controlling the synthesis of uridine diphosphoglucose dehydrogenase (4). When either strain is transformed with the DNA of the other, genetic recombination leads to correction of the defect in the synthesis of Type III capsular polysaccharide and fully capsulated Type III pneumococci are recovered.…”
Section: Phagocytosis Of C8 Pneumococci By Human Polymorpkonuclear Lementioning
confidence: 99%
See 1 more Smart Citation